Dynamic Transcriptomic Analysis of Breast Muscle Development From the Embryonic to Post-hatching Periods in Chickens - Liu, Jie; Lei, Qiuxia; Li, Fuwei; Zhou, Yan; Gao, Jinbo; Liu, Wei; Han, Haixia; Cao, Dingguo (Frontiers in Genetics, 2020)
Skeletal muscle development and growth are closely associated with efficiency of poultry meat production and its quality. We performed whole transcriptome profiling based on RNA sequencing of breast muscle tissue obtained from Shouguang chickens at embryonic day (E)12 and 17 to post-hatching day (D)1, 14, 56 and 98. A total of 9447 differentially expressed genes (DEGs) were filtered (Q < 0.01, fold change > 2). Time-series expression profile clustering analysis identified five significantly different expression profiles that were divided into three clusters. DEGs from cluster I with downregulated pattern were significantly enriched in cell proliferation processes such as cell cycle, mitotic nuclear division, and DNA replication. DEGs from cluster II with upregulated pattern were significantly enriched in metabolic processes such as glycolysis/gluconeogenesis, insulin signaling pathway, calcium signaling pathway, and metabolic pathways. DEGs from cluster III, with a pattern that increased from E17 to D1 and then decreased from D1 to D14, mainly contributed to fat metabolism. Therefore, this study may help us to explain the mechanisms underlying the phenotype that myofiber hyperplasia occurs predominantly during embryogenesis and hypertrophy occurs mainly after birth at the transcriptional level. These findings add to our knowledge of muscle development in chickens.